Design of improvement proposal for the reduction of waste through the 5s methodology and systematic layout planning under a kaizen environment in a bakery company in the food sector, 2022 (LACCEI, 2024)
The objective of this research is to determine the impact of the design of the improvement proposal through the 5S Methodology through the 5S Methodology and the Systematic Layout Planning technique under a KAIZEN environment for the reduction of waste from the bakery company. The methodology was quantitative, with a quasi-experimental design. The population evaluated was constituted by the total production time in working days, which are 2 per day, during the period from January to June of the year 2022, where 24 working days per month will be taken into account. Sampling was for convenience. The results obtained show a notable improvement that, if the 5S Methodology is correctly applied and implemented with commitment and discipline, will generate highly positive changes. In the case study, there was an average improvement of 70.16% more in all phases of said tool. . In summary, the correct application of the different resources will allow to have a control of the implementation, for this it is necessary to have periodic training for the personnel, and to be able to mitigate uncertainties, likewise to evaluate the compliance of what is proposed, it is necessary to carry out recurring internal audits.